Cultural Intelligence of Foreign Language Lecturers: A Measurement towards Global Competence - Devina Devina (Lingua Cultura, 2021)
The research measured the cultural quotient (CQ) of foreign language lecturers at Bina Nusantara University. Two major research strategies were applied: (1) a qualitative approach through the interview, and (2) a quantitative approach through CQ scale measurement. Firstly, the CQ scale developed by Ang et al. was tested on ten lecturers. Modifications were made to some test items to suit the context of foreign language teaching. Through the questionnaire, the analysis shows the mean and standard deviation of the overall test at M = 5,19 and SD = 1,7. For each domain of the scale, the analysis indicates that M = 5,16 and SD = 1,75 occurs for metacognitive domain, M = 4,4 and SD = 1,57 occurs for cognitive domain; M = 5,4 and SD = 1,6 occurs for motivational domain; and M = 5,5 and SD = 1,8 occurs for behavioral domain. Among ten lecturers, eight lecturers are considered to have high CQ, one lecturer to be medium CQ, and one lecturer to be low CQ. A further bivariate correlation analysis is then conducted to see the relationship between CQ lecturer’s background. The statistical data indicates no significant correlation found between CQ results and lecturer’s age (r = -0,575), time spent living abroad (r = -0,862), and time spent for teaching foreign language (r = -0,644). However, the further interview reveals that the experience of having relatives in a foreign country and living in a diverse cultural group shape lecturers’ paradigm in language teaching.